Cochlear Duct Length Calculation: Comparison Between Using Otoplan and Curved Multiplanar Reconstruction in Nonmalformed Cochlea. Issue 7 (August 2021) - Chen, Ying; Chen, Jianqing; Tan, Haoyue; Jiang, Mengda; Wu, Yingwei; Zhang, Zhihua; Li, Yun; Jia, Huan; Wu, Hao
Abstract : Objective: To describe a new method to measure the cochlear parameters using Otoplan software, and to compare it with the traditional method using curved multiplanar reconstruction (cMPR). Study Design: Retrospective analysis using internal consistency reliability and paired sample t test. Setting: Tertiary referral center. Patients: Thirty-four patients including 68 ears from a clinical trial were retrospectively reviewed. Main Outcome Measures: The length, width, height (distances A, B, H), and cochlear duct length of each cochlea were measured independently using two modalities: Otoplan and cMPR. Internal consistency reliability of the two modalities was analyzed. The time spent on each measurement was also recorded. Results: Otoplan software was compatible with all radiological data in this series. Distances A, B, and H showed no significant differences between Otoplan (9.33 ± 0.365, 6.61 ± 0.359, and 2.91 ± 0.312 mm) and cMPR (9.32 ± 0.314, 6.59 ± 0.342, and 2.93 ± 0.250 mm). The average cochlear duct length calculated by Otoplan was 34.37 ± 1.481 mm, which was not significantly different from that calculated by cMPR (34.55 ± 1.903mm, p  = 0.215). The measurements with Otoplan had better internal consistency reliability compared with those by cMPR, and measurements with a higher peak kilovoltage (140 kVp) CT scan showed further higher internal consistency reliability. Time spent on each cochlea by Otoplan was 5.9 ± 0.69 min, significantly shorter than that by cMPR (9.3 ± 0.72 min). Conclusion: Otoplan provides more rapid and reliable measurement of the cochlea than cMPR. Furthermore, it can be easily used in the laptop computer.